Analysis of the Impact of the Mining Sector on Regional Competitiveness in West Nusa Tenggara Province - Maulana Okta Saputra; Aryo Prawoto Wibowo; Fadhila Achmadi Rosyid (Green Publisher Indonesia, 2026)
The existence of mineral and coal resources in an area is often considered an advantage that can increase the competitiveness of the area. However, regions with large mining sector GDP do not always show high economic growth. For example, West Sumbawa Regency, which has a significant mining sector, only recorded an average economic growth rate of 3.19% between 2010 and 2023, placing it in the second lowest position in West Nusa Tenggara Province (NTB). This research aims to analyze the economic structure and sector shifts in each district in NTB using Location Quotient (LQ) and Shift Share analysis, as well as to form a Regional Competitiveness Index model with a Geographically and Temporally Weighted Regression (GTWR) approach. The results of the study show that the majority of districts in NTB have a base sector in the agricultural sector, except for West Lombok Regency in the transportation sector and West Sumbawa Regency in the mining sector. Sector shifts show different potentials, but the mining sector in areas that have not been massively exploited still has opportunities to be developed. The Regional Competitiveness Index model shows that the influence of the mining sector on competitiveness is not significant between regions with high and low mining sectors. In conclusion, excessive dependence on the mining sector can hinder economic growth and reduce regional competitiveness. It is important to maintain a balance between the development of the mining sector and other more sustainable sectors for stable and diversified economic growth.